Sustainability Marketing: Marketing Concepts in the Era of Sustainability - Somad, Abdul; Fatmawati, Fatmawati; Budhisusetyo , Amang; Zuhri, Zuhri (Devotion : Journal of Research and Community Service, 2025)
The conceptual issue of sustainable marketing is still a challenge, although this topic is increasingly discussed in the marketing literature. Terms such as sustainability marketing, sustainable marketing, and green marketing are often used interchangeably, causing confusion among academics and practitioners alike. This research aims to clarify the concept of sustainable marketing through discourse analysis of leading articles while identifying various approaches in its application. The research method used discourse analysis on 166 selected articles from the Scopus database which included the most influential publications. The analysis was carried out by categorizing theoretical and practical perspectives based on the framework of Hopwood et al. (2005). The findings of the study reveal three main approaches: Auxiliary Sustainability Marketing (ASM) which focuses on refining conventional marketing practices, Reformative Sustainability Marketing (RSM) which drives sustainable lifestyle changes, and Transformative Sustainability Marketing (TSM) which demands systemic transformation in social and economic institutions. This research makes an important contribution by presenting a clearer conceptual foundation for the development of sustainable marketing theory. For practitioners, the results of the research can be a guide in choosing an approach that is in accordance with the organization's sustainability goals. Going forward, further research is needed to test the effectiveness of each approach in a variety of different business contexts.